Scope and level of education are most crucial issues for survival of the biospherer and the mankind - Fedorkiv, A. I.; Perkun, І. V. (НТУ ДП, 2022)
Environmental technologies and other "environmental measures" for all their absolute and vital necessity are not able alone to solve the problem of the relationship between a humanbeingand the biosphere, and these problems are intertwined with the moral, and the latter already isrelevantto the humanities. The problem of creating a holistic theory determining the choice of human activity strategy needs a priority and urgent solution. But no theory directly related to finding ways leading to the prolonging the life of civilization can prevent a crisis without the integration of knowledge and education of people.
Keywords: освіта; человек; биосфера; гуманітарні науки